Comparison of two differentiation reagents for the staining of leprosy bacilli - WEN Xiao; LI Jiafeng; LI Guomin; PENG Wanqing; XUE Ruzeng (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To compare the effects of 20% sulfuric acid and acidic alcohol for the staining of leprosy bacilli in order to choose a better acid fast staining reagent for leprosy patients. Methods Sixty-one sections of the skin from leprosy patients were differentiated with either 20% sulfuric acid or acidic alcohol for 0.5, 1 and 1.5 minutes, respectively. The changes in bacterial colony count and red heterochromatic particles around the sweat glands were compared on the sections of the same block between these two methods. Results More bacterial colonies were observed using 20% sulfuric acid than acidic alcohol for all times (P=0.038, 0.012, 0.017, respectively). Differentiation with 20% sulfuric acid made it easier to observe heterochromatic particles in the sweat glands (P<0.001). Conclusion In the staining of leprosy bacillus, 20% sulfuric acid is better than acid alcohol to visualize bacterial colonies.